A Case Study Of CIMB Bank : The Merger Between Bumiputra- Commerce Holding Berhad (BCHB) And Southern Bank - Quah, Choon Leong (2009)
The case study highlights BCHB's strong intension to find a strategic fit in its mission, vision and objective to become a universal bank and Southern Bank, which strength is in the retail banking is the most suitable partner to strengthen BCHB's consumer banking business to complement its strong corporate banking business.